Non-parametric inference of impurity transport coefficients in the ASDEX Upgrade tokamak. (1st July 2022) - Nishizawa, T.; Dux, R.; McDermott, R.M.; Sciortino, F.; Cavedon, M.; Schuster, C.; Wolfrum, E.; von Toussaint, U.; Van Vuuren, A.Jansen; Cruz-Zabala, D.J.; Cano-Megias, P.; Moon, C.; et al.
Abstract: We present a non-parametric inference of impurity transport coefficients by using charge exchange recombination spectroscopy measurements of Ne X, Ne VIII, O VIII, and C VI lines. Due to their close atomic numbers, neon, oxygen and carbon impurity ions are assumed to have the same diffusion coefficient D and convection velocity v . Unlike conventional techniques that modulate or perturb the impurity contents, we employ a quasi-stationary plasma with static impurity profiles. Since the ratio of v to D only describes the equilibrated profile of the sum of all impurity charge states, steady-state measurements can still decouple D and v if different charge states are simultaneously observed. We have formulated a non-parametric analysis framework based on the Bayesian probability theory and conducted transport coefficient measurements for a Type III ELMy H-mode plasma at ASDEX Upgrade. The charge exchange reactions with the background neutrals, which are known to affect the impurity charge state balance, are taken into account by introducing additional free parameters. While D at the pedestal is close to the neoclassical level ( < 1 m s −2 ), a large diffusion coefficient and a strong outward convection are inferred right inside the pedestal top.